2006
DOI: 10.1096/fj.05-4382fje
|View full text |Cite
|
Sign up to set email alerts
|

Delayed GM‐CSF treatment stimulates axonal regeneration and functional recovery in paraplegic rats via an increased BDNF expression by endogenous macrophages

Abstract: Macrophages (monocytes/microglia) could play a critical role in central nervous system repair. We have previously found a synchronism between the regression of spontaneous axonal regeneration and the deactivation of macrophages 3-4 wk after a compression-injury of rat spinal cord. To explore whether reactivation of endogenous macrophages might be beneficial for spinal cord repair, we have studied the effects of granulocyte-macrophage colony stimulating factor (GM-CSF) in the same paraplegia model and in cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 55 publications
4
93
0
1
Order By: Relevance
“…Finally, whereas GM-CSF is most commonly associated with proliferation and differentiation of granulocytes and macrophages, there is accumulating evidence of its critical role in the central nervous system repair via expression of brain-derived neurotrophic factor, 37 a trophic factor that has been associated with psychiatric illness. This is consistent with broader evidence of a role for GM-CSF and IL-3 in the central nervous system, including neuroprotection, 38 communication across the blood-brain barrier, 39 and neurotransmitter modulation (particularly of acetylcholine and GABA levels).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, whereas GM-CSF is most commonly associated with proliferation and differentiation of granulocytes and macrophages, there is accumulating evidence of its critical role in the central nervous system repair via expression of brain-derived neurotrophic factor, 37 a trophic factor that has been associated with psychiatric illness. This is consistent with broader evidence of a role for GM-CSF and IL-3 in the central nervous system, including neuroprotection, 38 communication across the blood-brain barrier, 39 and neurotransmitter modulation (particularly of acetylcholine and GABA levels).…”
Section: Discussionmentioning
confidence: 99%
“…GM-CSF was also reported to activate microglia to release brain-derived neurotrophic factor (BDNF) that could induce neural regeneration after CNS injury [16]. We therefore investigated the effect of GM-CSF on the microglia/macrophage activation at 3 days, 1 week and 4 weeks after SCI by immunohistochemistry for CD11b, a marker of activated microglia/macrophages (Fig.…”
Section: Effect Of Gm-csf On the Microglia/macrophage Activation Aftementioning
confidence: 99%
“…Therapeutic effect of GM-CSF is already well known in the peripheral nervous system (PNS) injury by activating macrophages and Schwann cells to remove myelin debris [11][12][13]. Similarly, activation of microglia by GM-CSF is suggested to induce axonal regeneration and functional recovery after CNS injury either via phagocytosis of myelin debris or release of brain-derived neurotrophic factor (BDNF) [14][15][16]. Recently, we also reported that intraperitoneal (IP) injection of GM-CSF induced longterm functional recovery in rat SCI model [17] and in clinical trials combined with autologous bone marrow transplantation [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The improvement is probably due to the prevention of apoptosis of the cells, including neurons,46 via reduction of the expression of the proapoptotic proteins p53, p21, and Bax, and induction of nucleophosmin‐144 and the antiapoptotic protein B‐cell lymphoma 2 (Bcl‐2) 45. Additionally, GM‐CSF increased BDNF expression by macrophages, and subsequently stimulated axonal regeneration 49. Moreover, GM‐CSF suppressed glial scar formation,47, 48 activated dendritic‐like cells and neural stem cells (NSCs),53 and improved the survival of transplanted NSCs 50, 52.…”
Section: Roles Of Inflammatory Cytokines In Sci Repairmentioning
confidence: 99%